The effect of isoamyl alcohol and sec-octyl alcohol on the viscosity of coal water slurry. (15th May 2021) - Xu, Enle; Chen, Shixing; Dong, Yaping; Miao, Zhenyong; Jiang, Xiaofeng; Cui, Lifeng; Meng, Xianliang; Wu, Guoguang
Highlights: The amount of organic alcohol should be below to its solubility in CWS. CWS viscosity decrease first and then remain unchanged due to Isoamyl alcohol. Sec-octyl alcohol could decrease first and then increase the CWS viscosity. Abstract: In this work, the addition of isoamyl alcohol and sec-octyl alcohol on the viscosity of coal water slurry (CWS) was investigated and comprehensively analyzed. The surface tension, contact angle, dispersant absorbed amount, the microstructure of the particles as well as surface functional groups of coal powder was impacted by the addition of alcohols in the CWS. The isoamyl alcohol and sec-octyl alcohol lowers the surface tension and also partially absorbs to the coal particle surface, which would reduce the dispersant absorbed amount of the coal surface. The results show that both the isoamyl alcohol and sec-octyl alcohol can effectively reduce the viscosity of CWS under the amount of organic alcohol below to its solubility, and sec-octyl alcohol exhibits preferable performance than isoamyl alcohol. Our results anticipate to provide a convenient way to reduce CWS viscosity and could also be a reference for CWS preparation with such wastewater containing alcohol compounds.